Some parameters dependency on the effective secondary emission coefficient (ESEC)in microdischarge - Hamza Hussein, Salman; Jaseem, H. A.; Selman, T. A. (Al-Qadisiyah Journal of Pure Science, 2018)
The relations between the applied potential and electron current density, ion concentration near the cathode, field due to space charge and current multiplication factor are studied in microdischarge for noble gases. So, all these parameters studied at different values of the effective secondary emission coefficient ï§ for Argon gas. We found that all these parameters proportional inversely with ionization energy and increase with ï§ .